2006
DOI: 10.1016/j.bbamem.2006.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin-5 water channel in lipid rafts of rat parotid glands

Abstract: Aquaporin-5 (AQP5), an apical plasma membrane (APM) water channel in salivary glands, lacrimal glands, and airway epithelium, has an important role in fluid secretion. The activation of M3 muscarinic acetylcholine receptors (mAChRs) or alpha1-adrenoceptors on the salivary glands induces salivary fluid secretion. AQP5 localizes in lipid rafts and activation of the M3 mAChRs or alpha1-adrenoceptors induced its translocation together with the lipid rafts to the APM in the interlobular ducts of rat parotid glands.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 60 publications
2
32
0
5
Order By: Relevance
“…In addition, the Brij 98 treatment dramatically increased the amount of AQP0 and AQP5 in the low-density fraction. Increasing evidence supports the lipid raft localization of AQP5, [29][30][31] whereas the localization of AQP0 in lipid rafts has been reported previously. 16,17 These results suggest that Brij 98 provides better yields of lipid raft marker proteins in the low-density fractions; therefore, further studies were performed only on DRM isolated after Brij 98 solubilization.…”
Section: Isolation Of Lipid Raft-like Drmsmentioning
confidence: 93%
“…In addition, the Brij 98 treatment dramatically increased the amount of AQP0 and AQP5 in the low-density fraction. Increasing evidence supports the lipid raft localization of AQP5, [29][30][31] whereas the localization of AQP0 in lipid rafts has been reported previously. 16,17 These results suggest that Brij 98 provides better yields of lipid raft marker proteins in the low-density fractions; therefore, further studies were performed only on DRM isolated after Brij 98 solubilization.…”
Section: Isolation Of Lipid Raft-like Drmsmentioning
confidence: 93%
“…Although such a distribution is functionally important in potassium ion and water homeostasis, the mechanisms regulating the formation of these Kir4.1-and AQP4-enriched domains remain to be elucidated. AQP4 is associated with lipid raft-containing fractions in both brain and retina (27,35) as is another aquaporin, AQP5, that participates in fluid secretion in parotid gland cells (36). We therefore undertook a study to evaluate the role of lipid rafts in laminin-DG-dependent AQP4 clustering, and our data show that laminin induced a dramatic redistribution of GM1 into large cell surface clusters or macrodomains that colocalized extensively with ␤-DG and AQP4.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo experiments using confocal microscopy revealed that in the parotid gland under unstimulated conditions, AQP5 is located in lipid rafts that contain flotillins and prototypical ganglioside GM1 with a diffuse pattern in apical cytoplasm in duct cells. The activation of M 3 -and M 1 -mAChRs induces the rapid translocation of AQP5, together with lipid rafts, from the apical cytoplasm to the APM by enhancement of [Ca 2+ ]i [10,11]. AQP5 and lipid rafts are then released into saliva [12].…”
Section: Introductionmentioning
confidence: 99%